Bioarchaeological Notes on the Commingled Human Remains Held in the Church of Saint Francis of Paola, Sant’Angelo di Brolo, Sicily, Italy - Kemežytė, Aurelija; Piombino-Mascali, Dario (Acta medica Lituanica, 2022)
I this study, we examine human skeletal remains from the church of San Francis of Paola located in the small town of Sant’Angelo di Brolo, in the Italian region of Sicily. The preserved skeletal remains were temporarily transferred from their permanent resting place in the crypt for a macroscopic examination and evaluation. Various established methods were used to determine age at death, gender, any evidence of disease(s) as well as the fact that there was a minimum of 15 individuals. The findings were then subdivided into different groups of pathologies and recorded as individual cases. Amongst which, dental issues and cases of trauma were most prevalent. Additional conditions such as joint disease, congenital, metabolic and multifactorial disorders were also identified. The prevalence of dental decay indicates that the group’s diet consisted largely of carbohydrates, and that their oral hygiene was poor. Furthermore, evidence of trauma and poor healing suggested that the town was isolated from the main medical centres of the island. Severe complications of traumas linked with a loss of movement and overall independence, as well as physical pain, must have had a significant impact on the lives of those affected.